Extracting metal ions from basic oxygen steelmaking dust by using bio-hydrometallurgy - Tezyapar Kara, Ipek; Huntington, Victoria E.; Simmons, Nuannat; Wagland, Stuart T.; Coulon, Frederic (Elsevier, 2024)
This study aimed to optimise metal extraction from secondary hazardous sources, such as basic oxygen steelmaking dust (BOS-D). Initially, three batch systems approaches, including bioleaching using Acidithiobacillus ferrooxidans, chemical leaching using choline chloride-ethylene glycol (ChCl-EG) and a combined approach were compared. Then, scaling up was evaluated through a semi-continuous bioleaching column system with varied leachate recirculation over 21 days, focusing on Y, Ce, Nd, Li, Co, Cu, Zn, Mn, and Al. Bioleaching outperformed the control experiments within 3 days in the batch, demonstrating the key role of A. ferrooxidans. Chemical leaching conducted with a solid concentration of 12.5 % (w/v) successfully dissolved over 50 % of all metals within 2 h. For rare earth elements (REE), both bioleaching and hybrid leaching outperformed chemical leaching. However, considering factors such as process duration, overall efficiency, and ease of extraction, chemical leaching was the most effective method. Leachate recirculation reached a plateau after 11 days, resulting in extraction efficiency of 39 % when semi-continuous column set-up was used. Interestingly, variations in recirculation rates did not influence the extraction efficiency. Overall, this study emphasizes the considerable potential of bioleaching for metal recovery, but also highlights the need for further studies for enhancing permeability for percolation methods and optimisation, particularly in parameters such as aeration rate, when transitioning to larger scale systems.
Keywords: Bioleaching; Deep eutectic solvent; Metallurgical waste; Metal extraction; Biomining